Decoding the Dynamics of Sustainable Finance: Spillover, Risk, and Connectivity Through a Bibliometric Lens - Ke Peng; Muhammad Munir; Jifan Ren; Mariem Mejri (International Journal of Financial Studies, 2025)
The field of sustainable finance has grown rapidly in response to escalating climate and economic challenges, yet its intellectual landscape, especially the connectedness between green and traditional financial systems, remains underexplored. This paper aims to systematically map the evolution, thematic structure, and intellectual linkages of the sustainable finance literature with a specific focus on risk spillovers and connectedness across financial systems. This study employs a comprehensive bibliometric methodology to map 1261 Web of Science-indexed articles (1994–2024) on the connectedness of sustainable finance, using techniques such as citation analysis, bibliographic coupling, co-citation analysis, trend cartography, collaboration network, and keyword trend analysis. The study clarifies the field’s evolution and identifies its key themes, influential authors, institutions, and networks. The findings reveal an exponential surge in sustainable finance research after 2015, coinciding with policy milestones like the Paris Agreement and rising ESG investment interest. Notably, the review uncovers how research clusters have formed around topics such as green bond market spillovers, green technology innovation, and climate risk, highlighting both well-established areas and emerging fronts. The contribution lies in providing a roadmap for future research and policy: the study pinpoints knowledge gaps (e.g., systemic risk transmission between green and conventional assets) and suggests how policymakers and investors can leverage these insights to foster a resilient, sustainable financial system.